Situación del patrimonio moderno en Lima. Análisis de casos - Bustamante Pacheco, María Alejandra (2016)
This article was jointly developed by a group of students within the course of Built Heritage Conservation during 2015. Methodologically, students reviewed several publications of The Peruvian Architect magazine, dated from 1947 to 1960 with the intention of finding landmark buildings that may be contrasted with their current conditions. This resulted into a registration workshop which was finally recorded in the documents presented below.